Ahli Kitab dan Konteks Politik di Indonesia - Mujiburrahman, Mujiburrahman (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2017)
This writing describes the concept of “ahl al kitab” on the context of political aspect in Indonesia. The main purpose of the writing is to show the existence of ‘ahl kitab’ in relation to the political stage in Indonesia. The methodology of the writing is using normative approaches in order to be able to find out the extent of ‘ahli kitab’ on the context of political aspect in Indonesia. It is show that Islam gives a response to the existence of other religions. Muhammad prophet states that Islam is a continuity of previous religious. The discourse of ‘ahl al Kitab’ on political aspect in Indonesia is related to existence of this statement as a position in between secular and Islamic state. It is realize that the extent of ‘ahl kitab’ concept that covers all religions in Indonesia is still have a problem concerning the existence of religion and believe school that still illegitimate. In fact, the Muslim scholars in Indonesia are attempt to extent the concept of ‘ahl al Kitab’ in order the existence of other religions are accepted as will religions, including inter married religions.